Scientific Work Independence Application at Various Education Levels Referring to Piaget's Theory to Support the Implementation of Science Integrated Learning Model - Parmin, Parmin; Savitri, Erna Noor; Ifriza, Yahya Nur (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
The research specifically aims to create an application of scientific work independence instruments through Science Integrated Learning (SIL) for various education levels (primary, secondary, tertiary). The SIL model is applied in learning to find specific indicators for scientific work independence following students' development. This study applied the Research and Development methodology. Product testing was conducted in elementary schools, junior high schools, senior high schools, and universities. Based on the research results, SIL V1.0 App is a software developed based on mobile apps in the form of an Android application that is installable on a device with Android OS as the operating system. The application is named SIL V1.0 Apps, an acronym for Science Integrated Learning Application. The scientific work independence instrument developed by referring to Piaget's theory has a characteristic where the level of independence at each stage of scientific work is based on the development of children's learning psychology. Scientific work independence application at various education levels, which refers to Piaget's Theory, has more precise boundaries because it is adjusted to children's psychological development. The difference in learning independence level occurs because of the age difference.